Fabrication of Carbon nanotube-poly-methyl-methacrylate composites for nonlinear photonic devices - Martinez, Amos; Uchida, Sho; Song, Yong-Won; Ishigure, Takaaki; Yamashita, Shinji (OPTICAL SOC AMER, 2008)
Carbon nanotubes (CNT) are an attractive material for photonic applications due to their nonlinear optical properties, such as the nonlinear saturable absorption and high third order nonlinearity. However their utilization has been hindered by the lack of flexibility on the device design which rises from the current methods of Carbon nanotube deposition within the optical system. A suitable approach to solve this problem is to embed the CNTs in an optical material from which complex devices such as optical waveguides or optical fibers can be fabricated. Here, we propose a novel method to fabricate Carbon nanotube-doped poly-methyl-methacrylate (PMMA) composites in which the Carbon nanotubes are dispersed in the methyl-methacrylate (MMA) monomer solution prior to and during the polarization process. This method allows the bundle separation and dispersion of the CNT in a liquid state without the need for solvents, hence simplifying the method and facilitating the fabrication of volume CNT-PMMA. Volume fabrication makes this technique suitable for the fabrication of CNT-doped polymer fibers. In this paper, we also analyzed the merits of adding dopants such as diphenyl sulfide (DPS) and benzyl benzoate (BEN) to the CNT-PMMA composite and we observed that DPS plays the role of CNT dispersion stabilizer that can improve the device performance. The CNT-PMMA composite was employed to implement passive mode-locked laser. (C) 2008 Optical Society of America.
Keywords: SATURABLE ABSORBER; MODE-LOCKING; FIBER LASERS; MU-M